OCORRÃŠNCIA DE ð˜ð˜£ð˜¢ð˜ð˜ªð˜¢ sp. (HYMENOPTERA, IBALIIDAE) EM ð˜šð˜ªð˜³ð˜¦ð˜¹ ð˜¯ð˜°ð˜¤ð˜µð˜ªð˜ð˜ªð˜° F. (HYMENOPTERA, SIRICIDAE) NO RIO GRANDE DO SUL - Carvalho, A. G. de; Berti Filho, E.; Vadas, J.; Maia, J. L. da S. (REVISTA DE AGRICULTURA, 2020)
OCORRÃŠNCIA DE ð˜ð˜£ð˜¢ð˜ð˜ªð˜¢ sp. (HYMENOPTERA, IBALIIDAE) EM ð˜šð˜ªð˜³ð˜¦ð˜¹ ð˜¯ð˜°ð˜¤ð˜µð˜ªð˜ð˜ªð˜° F. (HYMENOPTERA, SIRICIDAE) NO RIO GRANDE DO SUL